ANALISIS MINIMNYA BUDAYA LITERASI SEKOLAH DASAR - Siti Aeti; Sumarno; Ida Dwijayanti (STKIP Subang, 2024)
Diara this 21st century school Already No foreign Again with application culture literacy , application culture literacy in public elementary schools Kubangjati 02 still very low, by Because That Head School embed Culture literacy For increase ANBK grade 5 scores , in terms of This writer use study Descriptive qualitative For know reason low Class 5 ANBK scores at State Elementary Schools Kubangjati 02 , writer use collection the data use visual analysis of the guidance instrument use interview And analysis the data form description narrative , from research data obtained reason low student's ANBK score class 5 , namely 1) low support student Guardian will culture literacy when student Already being at home 2) low interest read students 3) lack teacher references will outlook literacy 4) weak the use of ICT carried out by teachers when learning 5) lack collaboration between related teachers creating collaboration.6. minimal power library.so hinder development literacy at SDN Kubangjati 02.maka dari That head school appealed to all related _ with literacy to be able collaborate with OK, so capable increase The upcoming ANBK grade 5 scores are big hope mark Report card Education increase after everything Already capable collaborate in the field literacy with Good.